In vitro monitoring conformational changes of polypeptide monolayers using infrared plasmonic nanoantennas - Semenyshyn, Rostyslav; Neubrech, Frank (Nano letters, 2019)
Proteins and peptides play a predominant role in biochemical reactions of living cells. In these complex environments, not only the constitution of the molecules but also their three-dimensional configuration defines their functionality. This so-called secondary structure of proteins is crucial for understanding their function in living matter. Misfolding, for example, is suspected as the cause of neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease. Ultimately, it is necessary to study a single protein and its folding dynamics. Here, we report a first step in this direction, namely ultrasensitive detection and discrimination of in vitro polypeptide folding and unfolding processes using resonant plasmonic nanoantennas for surface-enhanced vibrational spectroscopy. We utilize poly-l-lysine as a model system which has been functionalized on the gold surface. By in vitro infrared spectroscopy of a single molecular monolayer at the amide I vibrations we directly monitor the reversible conformational changes between α-helix and β-sheet states induced by controlled external chemical stimuli. Our scheme in combination with advanced positioning of the peptides and proteins and more brilliant light sources is highly promising for ultrasensitive in vitro studies down to the single protein level.
Published: August 2, 2018
Gesehen am 23.07.2019